Relationship of Velopharyngeal Insufficiency With Face Mask Therapy in Patients With Cleft Lip and Palate. (January 2020) - Helal, Narmin; Ford, Matthew; Basri, Osama; Schuster, Lindsay; Martin, Brian; Losee, Joseph
Objective: To determine whether orthodontic/dentofacial orthopedic maxillary protraction face mask therapy induces changes in velopharyngeal functioning in a cohort of pediatric patients having cleft palate with or without cleft lip. Design: Retrospective chart review. Setting: A children's hospital in the United States. Participants: Forty-three pediatric patients with cleft palate, with or without cleft lip, syndromic or with isolated clefts, who received face mask therapy from January 2009 to April 2016. Intervention: Clinical data were extracted for review and analysis from medical records obtained from the Cleft Database/Research Registry (CDB-RR). Main Outcome Measures: Pittsburgh Weighted Speech Scores (PWSS) before and after therapy. Results: There was a significant increase in PWSS after face mask therapy for patients with a PWSS score of 0 prior to treatment. Patients with PWSS >0 before treatment remained largely stable after face mask therapy. Maxillary advancement was not significantly associated with change in PWSS or fistula presence/absence. Conclusions: There is an increased risk of velopharyngeal insufficiency with maxillary protraction face mask treatment in patients with cleft palate. Patient counseling and obtaining consent regarding speech changes during treatment are recommended.